1977
DOI: 10.2337/diab.26.11.1056
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Metabolism in Pregnancy: V. Interactions of Diabetes, Body Weight, Age, and High Carbohydrate Diet

Abstract: Plasma triglycerides increase two-to-three-fold in normal pregnancy. If mechanistically similar to the atherosclerosis-associated hypertriglyceridemias, hypertriglyceridemia in pregnancy should be exaggerated by diabetes, obesity, and high carbohydrate feeding. A failure to exaggerate would point to a different physiologic mechanism. To study this matter, we measured fasting plasma triglyceride and cholesterol In 38 normal, 22 gestational-diabetic, and 27 overtly diabetic women in the third trimester, measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 7 publications
(8 reference statements)
3
19
0
Order By: Relevance
“…While an increase in fetal body weight would be expected if the increased transpla cental transfer of glucose and fatty acids to the fetus were being assimilated by the fetus, fetal macrosomia in this model is not consis tently seen [45]. Nonetheless, these data sup port the hypothesis that increased plasma triglyceride concentrations in diabetic preg nancy [30] (also see below) may enhance fatty acid transport across the placenta through the permissive, sustained activity of placental LPL. The sustained activity of LPL in the placenta of pregnant diabetic rat is consistent with an insensitivity of other as pects of placental metabolism to perturba tions in maternal fuel physiology [46].…”
Section: Placental Lipoprotein Lipase Activity and The Effect Of Diabmentioning
confidence: 58%
See 2 more Smart Citations
“…While an increase in fetal body weight would be expected if the increased transpla cental transfer of glucose and fatty acids to the fetus were being assimilated by the fetus, fetal macrosomia in this model is not consis tently seen [45]. Nonetheless, these data sup port the hypothesis that increased plasma triglyceride concentrations in diabetic preg nancy [30] (also see below) may enhance fatty acid transport across the placenta through the permissive, sustained activity of placental LPL. The sustained activity of LPL in the placenta of pregnant diabetic rat is consistent with an insensitivity of other as pects of placental metabolism to perturba tions in maternal fuel physiology [46].…”
Section: Placental Lipoprotein Lipase Activity and The Effect Of Diabmentioning
confidence: 58%
“…As mentioned earlier, exaggerated hypertriglyc eridemia seems to be a feature of gestational [52][53][54] and overt type II diabetes in preg nancy [30,53,54] and HDL cholesterol tends to be reduced in those conditions [53,54], Examples of VLDL triglyceride and HDL cholesterol changes in type II diabetic pregnancy are presented in figure 12, show ing that levels can be abnormal in diabetic pregnancy and return to normal postpartum [53], Previous reports of type I diabetes in pregnancy [53,54], involving limited num bers of subjects, suggested that HDL choles-tcrol was increased in type I diabetes in preg nancy as it is in nonpregnant type I diabetic subjects [for review, see 55]. However, a re cent analysis by Van Allen et al [56] of a larger number of pregnant type 1 diabetics followed throughout gestation indicates that cholesterol in HDL and HDLi are both re duced throughout gestation.…”
Section: Effects Of Diabetes On Lipoproteinsmentioning
confidence: 97%
See 1 more Smart Citation
“…7 Women with GDM are at significantly increased risk of developing metabolic dysfunction after pregnancy including hyperlipidaemia. 8 Although many studies suggest that women with GDM have increased levels of triglycerides, LDL-C and total cholesterol and lower levels of HDL-C, these findings are generally inconsistent. 3 Alterations in maternal lipid metabolism are a normal part of pregnancy with an early accumulation of lipids in maternal tissue and the development of hyperlipidaemia in the latter half of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In a normal pregnancy, the compensatory mechanism by the pancreas makes up for the reduced effectiveness of insulin by increasing secretion of the hormone 26 . Plasma insulin levels are generally insufficient to prevent a certain degree of hyperlipidemia in normal pregnancy 27 . Estrogen has also been proven to increase endogenous production of VLDL TG, decrease adipose tissue lipoprotein lipase activity and hinder hepatic TG lipase activity 28 .…”
Section: Lipid Metabolism In Pregnancymentioning
confidence: 99%